Toward the Prognostic Significance and Therapeutic Potential of HER3 Receptor Tyrosine Kinase in Human Colon Cancer - Abdelhamid Beji; David Horst; Jutta Engel; Thomas Kirchner; Axel Ullrich (2011)
Abnormal accumulation and dysregulation of the epidermal growth factor receptor family member HER3 is associated with the development of various human cancers including those of the breast, lung, and ovary. We have previously shown that in melanoma HER3 is frequently overexpressed and is associated with poor prognosis. However, the importance of HER3 in colon cancer and its putative prognostic significance is still unknown.HER3 expression was analyzed in primary colon tumors from 110 patients by immunohistochemistry and correlated with time of progression. Parallel to this, the influence of HER3 overexpression on cell proliferation, migration, invasion, and apoptosis was investigated in four different colon cancer cell lines including DLD-1, LoVo, CaCO2, and T-84.HER3 was detected at high frequency and exclusively at the membrane of the primary tumors. Elevated HER3 expression levels may serve as a putative prognostic marker because it associates with cell proliferation and decreased time to disease progression. High HER3 protein expression as well as phosphorylation levels were detected in tested cells. HER3 downregulation by RNA interference abrogated cell proliferation, migration, and invasion. In addition, suppression of HER3 resulted in a G(2)-M cell-cycle arrest, induced apoptosis, and led to morphologic changes in colon cancer cell lines. Furthermore, application of a monoclonal antibody specific to the extracellular portion of the receptor reduced heregulin-β1-induced migration and invasion and also induced apoptosis in colon cancer cell lines.We postulate that HER3 is critically involved in colon cancer progression and may serve as a novel target for therapeutic intervention.